Prenatal–Postnatal Heavy Metal Exposure in Relation to Neurodevelopmental Disorder and ADHD: A Systematic Review - Gabriela Valencia Putri Husodho; Ichsan Marzuki Prasadah; Anatalya Diah Ayu Kumalasari; Talitha Aristawati Listiyanti; Rivaldo Heru Setiawan; Saekhol Bakri (Faculty of Medicine, Diponegoro University, 2025)
Introduction: Susceptibility to environmental insults during fetal brain development has been linked to an increased risk of neurodevelopmental disorders, including attention-deficit/hyperactivity disorder (ADHD). ADHD is a prevalent neurodevelopmental disorder in children and is influenced not only by genetics, but also by environmental factors, particularly prenatal exposure to heavy metals. Heavy metals, such as lead, mercury, cadmium, and arsenic, are known neurotoxins that can disrupt fetal brain development; however, evidence regarding their role in ADHD remains inconsistent.Methods: This systematic review followed PRISMA guidelines to evaluate the association between prenatal heavy metal exposure and the risk of ADHD in children. The PECO framework was used to define population, exposure, comparators, and outcomes. A comprehensive literature search was conducted across PubMed, ScienceDirect, and ProQuest, using relevant keywords. Eligible studies included human observational research (cohort, case-control, cross-sectional) between 2021 and 2025 assessing prenatal exposure to heavy metals, neurodevelopmental outcomes, and ADHD.Results: Several studies have reported that elevated prenatal levels of cadmium, lead, and manganese are associated with increased ADHD symptoms and reduced cognitive performance. The findings on mercury were mixed, potentially due to confounding factors, including fish intake and maternal nutrition. Selenium and copper demonstrate dual effects, being essential at low levels but harmful at high concentrations. Thallium exposure in the third trimester significantly impaired cognitive and psychomotor development. Some studies have highlighted sex-specific and nonlinear dose-response effects.Conclusion: Heavy metals have an inconsistent impact on neurodevelopment. While some studies have associated prenatal exposure to cadmium and lead with neurodevelopmental issues, others have not found such links. Both prenatal and postnatal exposure to heavy metals, particularly cadmium, mercury, and lead, are associated with childhood ADHD.Keywords: ADHD, prenatal exposure, heavy metals, neurodevelopment, environmental toxins